Chronic Exposure to Malaria Is Associated with Inhibitory and Activation Markers on Atypical Memory B Cells and Marginal Zone-Like B Cells - Ubillos, Itziar; Campo, Joseph J.; Requena, Pilar; Ome-Kaius, Maria; Hanieh, Sarah; Rose, Honor; Samol, Paula; Barrios, Diana; Jiménez, Alfons; Bardají, Azucena; Mueller, Ivo; Menéndez, Clara; et al. (Frontiers in Immunology, 2017)
In persistent infections that are accompanied by chronic immune activation, such as HIV, HCV and malaria, there is an increased frequency of a phenotypically distinct subset of memory B cells lacking the classic memory marker CD27 and showing a reduced capacity to produce antibodies. However, critical knowledge gaps remain on specific B cell changes and immune adaptation in chronic infections. We hypothesized that expansion of atypical memory B cells (aMBC) and reduction of activated peripheral marginal zone (MZ)-like B cells in constantly exposed individuals might be accompanied by phenotypic changes that would confer a tolerogenic profile, helping to establish tolerance to infections. To better understand malaria-associated phenotypic abnormalities on B cells, we analyzed PBMCs from 55 pregnant women living in a malaria-endemic area of Papua Nueva Guinea and 9 Spanish malaria-naïve individuals using four 11-color flow cytometry panels. We assessed the expression of markers of B cell specificity (IgG, IgM), activation (CD40, CD80, CD86, b220, TACI, CD150), inhibition (PD1, CD95, CD71) and migration (CCR3, CXCR3, CD62l). We found higher frequencies of active and resting aMBC and marked reduction of MZ-like B cells, although changes in absolute cell counts could not be assessed. Highly exposed women had higher PD1+, CD95+, CD40+, CD71+ and CD80+ activated aMBCs frequencies than non-exposed subjects. Malaria exposure increased frequencies of b220 and pro-apoptotic markers PD1 and CD95, and decreased expression of the activation marker TACI on MZ-like B cells. The increased frequencies of inhibitory and apoptotic markers on activated aMBCs and MZ-like B cells in malaria-exposed adults suggests an immune homeostatic mechanism for maintaining B cell development and function while simultaneously down-regulating hyperreactive B cells. This mechanism would keep the B cell activation threshold high enough to control infection but impaired enough to tolerate it, preventing systemic inflammation.